Cartographic methods of presentation the average transaction prices of the undeveloped land = Kartograficzne metody prezentacji średniej ceny transakcyjnej gruntów rolnych niezabudowanych - Ogryzek, Marek; Ciski, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a description of basic cartographic methods used to visualize spatial data. Information on average transaction prices of the undeveloped land in Warmińsko-Mazurskie voivodeship, from The Agricultural Property Agency, Regional Office in Olsztyn, was the basis for map creation. Unified data allows the accurate presentation of information and highlights the differences in selected cartographic methods.
Keywords: cartographic methods; spatial data; transactions prices; undeveloped land; metody kartograficzne; dane przestrzenne; cena transakcyjna; grunty rolne niezabudowane